Comorbidities in Chilean patients with psoriasis: a Global Healthcare Study on Psoriasis. (1st December 2022) - Valenzuela, Fernando; De La Cruz, Claudia; Lecaros, Cristóbal; Fernández, Javier; Hevia, Gonzalo; Maul, Lara Valeska; Thyssen, Jacob P.; Vera‐Kellet, Cristián; Egeberg, Alexander; Armijo, Daniela; Pizarro, Cristian; Riveros, Tatiana; et al.
Abstract: Background: Psoriasis is a chronic inflammatory skin disease associated with several important medical comorbidities. There are scant data available on the comorbidities of patients with psoriasis in South America. Aim: To examine the comorbidity profile of adult patients with psoriasis in Chile and its association with severity of psoriasis. Methods: This was a multicentre, cross‐sectional study involving 16 hospitals and clinics in Chile, which used a 48‐item questionnaire to study clinician‐ and patient‐reported outcomes and comorbidities. Inferential analyses were performed by psoriasis severity, using Fisher exact test, Student t‐test and multivariable logistic regression. Results: In total, 598 adult patients with psoriasis were included (51.1% male; mean age 49.2 ± 15.1 years); 48.5% mild and 51.4% moderate to severe; Psoriasis Area and Severity Index 11.6 ± 11.5; body surface area 14.7 ± 18.2%. Plaque psoriasis was the most common phenotype (90.2%), followed by guttate (13.4%). Psoriatic arthritis occurred in 27.3% of patients. Comorbidities were reported in 60.2% of all patients with psoriasis. Frequent concomitant diseases were obesity (25.3%), hypertension (24.3%), Type 2 diabetes mellitus (T2DM) (18.7%), dyslipidaemia (17.4%), metabolic syndrome (16.7%) and depression (14.4%). After adjustment, significant associations were found between moderate to severe psoriasis and obesity, T2DM and nonalcoholic fatty liver disease (NAFLD) compared with mild psoriasis. Conclusions: We report a large study of comorbidities, including depression, dyslipidaemia, T2DM and NAFLD, in people with psoriasis in Chile. The prevalence of comorbidities with psoriasis in Chile appears similar to that found in Western countries, and emphasizes the importance of assessing patients with psoriasis for risk factors for and presence of, comorbid disease in a multidisciplinary setting. Abstract : There are scant data available on the comorbidities of patients with psoriasis in South America. Multicentre, cross‐sectional study involving 16 hospitals and clinics in Chile utilized a 48‐item questionnaire to study clinician and patient reported outcomes and comorbidities. In total, 598 adult patients with psoriasis were included. Comorbidities were reported in 60.2% of all patients with psoriasis. Frequent concomitant diseases were obesity (25.3%), hypertension (24.3%), Type 2 diabetes (18.7%), dyslipidaemia (17.4%), metabolic syndrome (16.7%) and depression (14.4%). Significant associations were found between moderate to severe psoriasis and obesity, type 2 diabetes and nonalcoholic fatty liver disease compared with mild psoriasis.